2005
DOI: 10.1002/ijc.21536
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen and contralateral breast cancer in BRCA1 and BRCA2 carriers: An update

Abstract: Women with a mutation in BRCA1 or BRCA2 face a lifetime risk of breast cancer of 80%, and following the first diagnosis the 10-year risk of contralateral breast cancer is 30%. It has been shown that both tamoxifen and oophorectomy prevent contralateral breast cancer, but it is not clear whether there is a benefit in giving tamoxifen to women who have previously undergone an oophorectomy. Furthermore, the relative degree of protection in BRCA1 and BRCA2 carriers has not been well evaluated. We studied 285 women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
123
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(134 citation statements)
references
References 21 publications
7
123
2
2
Order By: Relevance
“…Tamoxifen has been associated with a reduction in second primary breast cancer in BRCA1 or BRCA2 mutation carriers, and nonadherence in this setting is associated with a young age (<40 years; refs. 34,35). Of interest, smoking (36) and young age (37) have been associated with nonadherence to breast cancer screening.…”
Section: Healthy High Risk/preventionmentioning
confidence: 99%
“…Tamoxifen has been associated with a reduction in second primary breast cancer in BRCA1 or BRCA2 mutation carriers, and nonadherence in this setting is associated with a young age (<40 years; refs. 34,35). Of interest, smoking (36) and young age (37) have been associated with nonadherence to breast cancer screening.…”
Section: Healthy High Risk/preventionmentioning
confidence: 99%
“…The effect of tamoxifen on contralateral breast cancer has been studied in a case-control study of BRCA1 and BRCA2 mutation carriers (Gronwald et al, 2006). The multivariate OR for contralateral breast cancer associated with tamoxifen use was 0.50 for carriers of BRCA1 mutations (95% CI: 0.30-0.85) and was 0.42 for carriers of BRCA2 mutations (95% CI: 0.17-1.02), implying a risk reduction of 50% or more.…”
Section: Tamoxifen and Raloxifenementioning
confidence: 99%
“…El-Harith et al concluded from their study that BRCA1 and BRCA2 mutations are likely to contribute to the pathogenesis of familial BC in Saudi Arabia (El Harith et al, 2002). Women at high risk would benefit from genetic counseling that helps patients or family members make informed decisions about genetic testing and that enhances selection of early cancer detection and/or risk-reduction strategies (The United States Preventive Services Task Force 2005 and the National Comprehensive Cancer Network 2008; Schwartz GF et al 2008;Gronwald J et al 2006).…”
Section: Introductionmentioning
confidence: 99%